Nursing staff perception of nursing on approach to child hospitalized ludica - Ana Cláudia Seus Falke; Viviane Marten Milbrath; Vera Lucia Freitag (Universidad de Alicante, 2018)
Objective: To know the perception of the nursing team about the playful approach to hospitalized children. Methodology: exploratory-descriptive qualitative study in Pediatrics in a hospital in southern Rio Grande do Sul School with eight nursing team professionals. To collect data, we used the semi-structured interview. The information was interpreted through thematic analysis of Minayo. Results: it was observed that the nursing staff does not have the technical and scientific preparation to use a playful approach in providing nursing care, as well as some ignorant of the concept and the techniques applied to the play therapy, this issue has had little or no approach in academic or vocational training of respondents. Conclusion: it is necessary that this mode is entered in undergraduate courses and that the institutions promote playful care that professionals can use this instrument care, thereby improving the care provided to hospitalized children.